Comparative study between tactile electrosurgical ablation guided by rectal ultrasound and versapoint hysteroscopic ablation in cases of perimenopausal uterine bleeding - Mohamed El-kholy; Faisal A Mustafa; Mahmoud A Badawy (Wolters Kluwer Medknow Publications, 2021)
Background and aim Bleeding is considered one of the most common problems in perimenopausal women. The menopausal transition is an imprecise period and can be established from the moment of appearance of menstrual disturbances and elevation of the serum follicle-stimulating hormone (FSH) level. The objective of this study was to evaluate the efficacy of tactile electrosurgical ablation of endometrium under rectal ultrasound guidance versus modified tactile versapoint hysteroscopic ablation in the management of perimenopausal abnormal uterine bleeding. Patients and methods This study was conducted in the Department of Obstetrics and Gynecology of Al-Azhar University Hospital (Assuit), Egypt on 50 perimenopausal patients with abnormal uterine bleeding. Patients were divided into two groups according to the method used. Group 1 included 25 participants, and ablation was done using tactile ablation guided by rectal ultrasound. Group 2 included 25 participants, who underwent hysteroscopic ablation using versapoint hysteroscope. Results Regarding sociodemographic study data, age in both groups ranged from 38 to 45 years, with P value of 0.903. Parity also showed no statistically significant difference between both groups. The incidence of complication was more in group 1 but less dangerous. Thermal injury of genital tract was seen in two cases in group 1 but no cases in group 2, with P value of 0.245. Cervical injury was seen in two cases in group 1 and one case in group 2, with P value of 0.500. Perforation occurred in two cases in group 1 and one case in group 2, with P value of 0.500. Regarding specific complication of endometrial ablation by versapoint hysteroscopic ablation, which occurred in group 2 only, by distension media, four cases had complications such as hyponatremia (decrease in serum sodium of 10 mmol/l). Postoperative complication such as hematometra occurred in one case only in group 1, with P value 0.500. The cost range in group 1 was from $14 to 20 and in group 2 it was from $40 to 50, with P value less than 0.001FNx08. The time of surgery ranged from 10 to −15 min in group 1 and from 20 to 30 min in group 2, with P value less than 0.001FNx08. After 6 months, two cases came back with recurrent Hge in group 1 and six cases in group 2, with P value 0.123. Conclusion Tactile ablation is easier, effective, and less costly.